Champion of freedom : Dietrich Bonhoeffer - Martin, Michael, 1948- (Greensboro, N.C. : Morgan Reynolds Pub., 2012)
Chronicles the life of the German pastor who opposed Nazi anti-Christian policies and, after being exposed as a conspirator in the plot to assassinate Hitler, died at the Flossenbürg concentration camp in 1945.
Includes bibliographical references and index.
Keywords: Theologians -- Juvenile literature